PENGARUH MODEL PEMBELAJARAN THINK PAIRS SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH DI MATERI PECAHAN KELAS IV SDN 89 SINGKAWANG - Nurkhusnasari, Nurkhusnasari; Fitriyadi, Slamat; Kariadi, Dodik (MES: Journal of Mathematics Education and Science, 2024)
This research aims to determine whether there is an influence of the TPS (Think Pairs Share) learning model on problem solving in fourth grade fraction material at SDN 89 Singkawang. The type of research used is quantitative research with a true experimental design method. The population in this study was 35 class IV students at SDN 89 Singkawang. Then samples were taken using a purposive sampling technique so that the sample used was 35 students consisting of class IV. The sample used in the research was carried out by selecting samples taking into account the students' cognitive results, so that researchers could produce class IV for the experimental class and control class. The prerequisite test carried out is a normality test using the Chi-square formula and a variance homogeneity test is carried out to see the similarity of the variants in the two groups. To test the first hypothesis, the Effect Size formula is used and to test the second hypothesis, the t-test formula is used. The results of the research show that: 1) The TPS (Think Pairs Share) learning model has an effect on problem solving abilities in class IV fraction material at SDN 89 Singkawang. This is shown from the calculation of the Effect Size value, which is 1,600, which is included in the high criteria. 2) There is a difference in problem solving abilities using the TPS (Think Pairs Share) model with the conventional model in class IV fraction material at SDN 89